Faktor-faktor yang mempengaruhi fertilitas di Kampung Keluarga Berencana (KB) di Kecamatan Muara Bulian Kabupaten Batanghari - Prayanti, Novi; Zulfanetti, Zulfanetti; Junaidi, Junaidi; Wahyuni, Ira (Jurnal Paradigma Ekonomika, 2021)
The purpose of this study was to determine the profile of the Family Planning Village in Muara Bulian District, Batanghari Regency, to determine the characteristics of EFA in the Family Planning Village in Muara Bulian District, Batanghari Regency, to analyze the influence of the level of age at first marriage, family income, education, employment status. in Muara Bulian District, Batanghari Regency. The analytical tool used descriptive analysis to analyze data by describing or describing the data and multiple regression analysis. The results of the analysis of this study are that the results of the research that have been carried out on the factors that influence fertility in the Family Planning Village of Batanghari Regency, it is found that the Age of First Marriage, women who have a fertility opportunity of more than 2 have an essential effect in increasing the birth rate. Income, women with a fertility opportunity of more than 2 have an important influence in improving fertility. Junior high school education, in this study, women who have low education do not affect the opportunity to increase fertility. SLTA + education, in this study, women who have higher education do not affect increasing fertility. Employment status, in this study, women who work do not affect increasing fertility. Â 